Analysis of acoustics surface wave reflection on the interdigital transducer - FILIPIAK, J. (Archives of Acoustics, 1990)
By applying the equivalent scheme, the analysis of the acoustics surface wave reflection from the interdigital transducer has been carried out. The explicit form of the coefficient of reflection was found, from which the following terms have been separated – the magnitude of the mechanical wave reflection due to variation of the acoustics impedance in the area of transducer, and magnitude of the wave regeneration by the electrically loaded transducer. The results of calculations has been presented for the coefficient of surface wave reflection from the simple transducer with single and double electrodes as a function of its electrical load. The experimental verification has been undertaken for transducers on LiNbO3.